Strategies for Improving Public Service Quality Through Good Governance Principles at the Danau Keliling Subdistrict Office - Al Sunah, M Dhany; Maidastri, Rini; bustami, Edwin (International Humanity Advance, Business & Sciences, 2025)
The background of this research is the application of the principle of good governance, which is suspected to be still not good. The purpose of this research is to find out how to implement the strategy to improve the quality of public services through the principle of good governance at the Keliling Danau District Head Office, Kerinci Regency, which is focused on the principles of Accountability, Responsiveness and Participation in the Keliling Danau District Office, Kerinci Regency. This type of research is Qualitative research. The activities in data analysis in this research are data collection, data reduction, data presentation, and conclusion. The informant selection technique in this study was carried out by purposive sampling (selected sample). The researcher selected the informant based on the criteria that had been determined and the research objectives. The research findings show that the principles of good governance, including participation, accountability, and responsiveness, have been well implemented by the Keliling Danau District sub-district office employees, but these principles must still be improved.